Depression and fatigue in active IBD from a microbiome perspective: a Bayesian approach to faecal metagenomics - Thomann, Anne K.; Wüstenberg, Torsten; Wirbel, Jakob; Knödler, Laura-Louise; Thomann, Philipp; Zeller, Georg F.; Ebert, Matthias; Lis, Stefanie; Reindl, Wolfgang (BMC medicine, 2022)
Background:  Extraintestinal symptoms are common in inflammatory bowel diseases (IBD) and include depression and fatigue. These are highly prevalent especially in active disease, potentially due to inflammation-mediated changes in the microbiota-gut-brain axis. The aim of this study was to investigate the associations between structural and functional microbiota characteristics and severity of fatigue and depressive symptoms in patients with active IBD. - Methods:  We included clinical data of 62 prospectively enrolled patients with IBD in an active disease state. Patients supplied stool samples and completed the questionnaires regarding depression and fatigue symptoms. Based on taxonomic and functional metagenomic profiles of faecal gut microbiota, we used Bayesian statistics to investigate the associative networks and triangle motifs between bacterial genera, functional modules and symptom severity of self-reported fatigue and depression. - Results:  Associations with moderate to strong evidence were found for 3 genera (Odoribacter, Anaerotruncus and Alistipes) and 3 functional modules (pectin, glycosaminoglycan and central carbohydrate metabolism) with regard to depression and for 4 genera (Intestinimonas, Anaerotruncus, Eubacterium and Clostridiales g.i.s) and 2 functional mod‑ules implicating amino acid and central carbohydrate metabolism with regard to fatigue. - Conclusions:  This study provides the first evidence of association triplets between microbiota composition, func‑tion and extraintestinal symptoms in active IBD. Depression and fatigue were associated with lower abundances of short-chain fatty acid producers and distinct pathways implicating glycan, carbohydrate and amino acid metabolism. Our results suggest that microbiota-directed therapeutic approaches may reduce fatigue and depression in IBD and should be investigated in future research.
Gesehen am 13.02.2022